LEARNING MODEL THROWS CATCH IN ELEMENTARY SCHOOL CHILDREN OF LOWER GRADE AGE - Putra Arya Dinata Arya; Widiastuti; Hernawan (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to produce a catch and catch learning model for elementary school students. This study used a research and development method by Borg And Gall by using 10 stages where the subjects in this study were elementary school students of lower class age in the Kepahiang district. This study produced 21 Throw Catch Learning Models which are effective for improving the learning outcomes of catch and catch in elementary school students where this learning model has been validated first by a validation team consisting of one physical education teacher and two physical education teachers, based on the results of the small group test. and the results of the large group test of the learning model developed were declared valid and feasible to be used in catch-catch learning.